Hooliganism and police tactics: should tear gas make crime preventers cry? - Panu Poutvaara; Mikael Priks (Institute for the Study of Labor (IZA), 2007)
Hooliganism is on the rise and different countries use different strategies to combat it. We introduce a model where hooligans reap utility from violence and social identity and study the effects of different police strategies. We find that an increase in discriminative policing, provided by intelligence units, for example, always reduces violence. Under the right circumstances, it may also lead to larger supporter clubs and a significant drop in violence. Indiscriminate policing, such as the use of teargas or random jailing of potential law breakers, may, however, backfire and result in smaller and more brutal groups.
urn:nbn:de:101:1-20080401188
Keywords: 330; Gewalt; Soziale Gruppe; Kriminalpolitik; Spieltheorie; Theorie